Enhancing Critical Thinking Skills through Group Investigating Models and “Datar” “Pakar” Media for Facing the 21st Century - Utaminingsih, Esty Setyo; Irchamni, Achmad; Utami, Yeri; Shabrina, Monita Nur (The Journal of Educational Development, 2024)
The critical thinking skills of fourth-grade elementary school students have been found to be lacking, hindering their ability to effectively process information. This research aims to explore the impact of group investigation learning models supported by “Datar” and “Pakar” media on enhancing critical thinking skills in social science education. Employing an experimental "One-Shoot Case Study" method, the study involved pre-testing students, implementing the group investigation model with the media tools, and post-testing to measure improvements. Data were analyzed using the N-Gain formula. The results indicated a significant enhancement in students' critical thinking abilities, with an average N-Gain score of 0.61, categorized as moderate improvement. The study concluded that the integration of innovative learning models and interactive media significantly contributes to developing critical thinking skills essential for 21st-century education. This research underscores the importance of active, collaborative, and media-supported learning approaches in elementary education, offering valuable insights for educators and contributing to the advancement of educational methodologies aimed at fostering critical thinking skills in young learners.